The betrayal - Lewis, Beverly, 1949- (Lewis, Beverly, 1949- Abram's daughters, 2003)
Sadie, the oldest daughter in an Amish family, prefers the "English" world to her Amish life. When her traditional rumschpringe goes awry before her baptism, both Sadie's life and her sister Leah's may be forever changed.